Degloving Penile Injury with Urethral Avulsion: A Case Report - S, Sivanandhan; L, Sivaneswaran (IIUM Medical Journal Malaysia, 2019)
Accidental male genital injuries represent a serious urological disorder that demands immediate urological treatment due to risk of infection and need for fertility preservation. We reported a 30- year-old gentleman who presented with an extensive penile degloving injury, right open pneumothorax and right thigh laceration following a buffalo attack. Examination under anesthesia (EUA) demonstrated ruptured penis with tearing up to penile base and partially avulsed right testis. Right orchidectomy, wound debridement and suprapubic catheter insertion performed before being referred to Penang General Hospital. Repeated EUA revealed avulsed penile urethra 3cm from the meatus with interposing granulation tissue of 2cm in length. He underwent serial wound debridement and eventually required a split skin graft to the penis. Patient was reported to be able to achieve penile erection by 2 months post-operative and planned for urethroplasty later. This is the first paper that reports an incident of buffalo attack resulting in degloving injury of penis. Management depends on severity of trauma and prompt intervention essential to prevent immediate as well as delayed complication. Urethral injury must be considered in any extensive penile injury. Despite multiple modality for traumatic penile skin loss repair, split thickness skin grafting (SSG) was chosen for this patient. Conclusion: External injuries of the genitals, particularly caused by animal attack, should be followed by immediate operative exploration and if necessary, to reparative measures. Care must be taken with goal of optimizing long term sexual, cosmetic and voiding outcomes.